Effect of jujube pulp on rennet-induced coagulation properties of milk with different fat contents. (May 2023) - Wang, Fang; Tian, Shiyu; Fan, Wanning; Sun, Xuemei
Abstract: The effect of jujube pulp on rennet-induced coagulation of milk with different fat contents was investigated. Whole, reduced-fat and skim milk were mixed with concentrated jujube pulp in different percentages (100:0, 90:10, 80:20, 70:30, w/w); addition of jujube pulp advanced the time point at which elasticity index began to increase, decreased the elasticity index at any given time during renneting, increased the moisture content and curd yield, disrupted the protein network, and reduced hardness, springiness and storage modulus of the curds. However, the curd colour was non-uniform with 10% jujube pulp, but became a uniform "date-red" colour with higher jujube pulp concentrations. Moreover, sensory characteristics of reduced-fat and skim milk curds were inferior to those from whole milk, whereas jujube pulp significantly improved sensory characteristics of the former, especially their hardness, smoothness and jujube flavour. This study has highlighted the potential of jujube pulp for producing unique-flavoured cheese-like products.